Engineering a noise-free quantum memory for temporal mode manipulation - Hird, TM (2021)
An optical quantum memory, a device which can store and retrieve on demand an arbitrary quantum state at the single photon level, has been identified as a significant cornerstone of photonic quantum technologies. The development of such a memory would allow the creation and development of a large number of quantum technologies. These would range from the ability to synchronise processing steps in an optical quantum computer, to the construction of a quantum repeater which would allow faithful transmission of quantum states over arbitrarily long distances. In this thesis I investigate broadband light storage in a room-temperature Raman memory for purposes of quantum information processing with photons. During the course of this thesis, a novel scheme to suppress four-wave mixing noise is simulated, based on equations derived to describe the physics of the memory interaction. The experimental arrangement to test the suppression method is described and an original method using photon statistics is demonstrated. The results of these experiments prove the ability of the memory to retrieve and maintain the non-classicality of the state, given a single photon input.